Respostas
respondido por:
73
(-1)^0 = 1
(-1)^1 = -1
(-1)^2 = 1
(-1)^3 = -1
então, (-1) elevado a um número par é 1, e a um número ímpar é -1
então:
A = (-1)^100 = 1
B = (-1)^101 = -1
A + B = 1 + (-1) = 1 - 1 = 0
A - B = 1 - (-1) = 1 + 1 = 2
é isso, até mais
(-1)^1 = -1
(-1)^2 = 1
(-1)^3 = -1
então, (-1) elevado a um número par é 1, e a um número ímpar é -1
então:
A = (-1)^100 = 1
B = (-1)^101 = -1
A + B = 1 + (-1) = 1 - 1 = 0
A - B = 1 - (-1) = 1 + 1 = 2
é isso, até mais
respondido por:
33
(-1) * 100 = -100 = a
(-1) * 101 = -101 = b
a)-100 + -101 = -201
b)-100 - -101 = 1
(-1) * 101 = -101 = b
a)-100 + -101 = -201
b)-100 - -101 = 1
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás